Hipogalactia inicial, fatores de risco para o desmame precoce e promoção do aleitamento materno em primíparas atendidas em um Hospital Amigo da Criança no Brasil - Beatriz de Oliveira Rocha (2018)
Background: Hypogalactia or delayed lactogenesis II, defined as delayed copious milk production for more than 72 hours postpartum is a frequent cause of early weaning. Research Aims/Questions: To evaluate the frequency of and factors associated with delayed lactogenesis II. As well as, its association with exclusive breastfeeding cessation in a population of primiparas seen at a Baby-Friendly Hospital of the Brazilian public health system, besides the identification of care actions which may promote longer duration of breastfeeding in this population. Methodology: Prospective observational study with 224 mothers and full-term newborns. Social and demographic data, prenatal care, as well as peripartum and postnatal hospital care for breastfeeding promotion were collected in the maternity ward within 24 hours postpartum through an interview with mothers and medical records analysis. The occurrence of lactogenesis II was identified on day 4 postpartum from maternal report of changes in the breast and milk. Information on the management of breastfeeding after hospital discharge was collected on day 7 in person and day 14 after delivery by phone call. Descriptive analysis was performed with Kolmogorov-Smirnov and frequency tables. Bivariate analyzes were performed with MannWhitney, Spearman, Chi-square and Fisher's Exact tests. Poisson regression with robust variance and multivariate logistic regression, both with backward selection, identified factors associated with delayed lactogenesis II and exclusive breastfeeding cessation on days 7 and 14 postpartum. Results: Delayed lactogenesis II occurred in 18.8% of the mothers and was associated to increased mother´s age (IRR: 1.081, 95% CI: 1.039 - 1.125), alcohol consumption during pregnancy (IRR: 2.710, 95%: 1.469 - 4.996), formula supplementation during hospital stay (IRR: 3.285, 95% CI: 1.756 6.147) and score 10 on the Edinburgh Postpartum Depression Scale (IRR: 2.467, 95%IC: 1.378 4.419). The weaning rate was 16% on day 7 and 25% on day 14. Delayed lactogenesis II (OR: 4.121, IC95% 1.794 - 9.472); use of dummies (OR: 3.904, IC95% 1.837 - 8.295); late onset of skin-to-skin contact (OR: 1.343, IC95% 1.017 - 1.778) and scores < 60 on the Breastfeeding Self Efficacy Scale (OR: 1.031, IC95% 1.004 - 1.058) are associated to weaning on day 7. Use of dummies (OR: 5.071, 95%IC: 2.439 10.541), delayed lactogenesis II (OR: 3.245, 95%IC: 1.450 7.263 and scores < 60 on Breastfeeding Self Efficacy Scale (OR: 2.427, 95%IC 1.170 5.035 are associated with weaning on day 14 postpartum. Among breastfeeding promotion actions recommended by the Baby-Friendly Hospital Initiative, it was identified a lower frequency of implementation in practices referring to steps 3,5,8 and 10 in this population. Conclusion: Delayed onset of lactogenesis II is a risk factor for early weaning. Older mothers who consumed alcohol during pregnancy and who present risk or history of postpartum depression should be identified during prenatal care and followed up during the first week postpartum for the diagnosis and correct management of difficulties in establishing lactation. Supplementation with infant formulas should be judicious. Breastfeeding promotion practices widely spread such as skin-to-skin contact right away for an hour after delivery should be strengthened and the use of pacifiers in breastfed term infants should be avoided. The use of standardized scales can help health professionals to identify mothers at greater risk of postpartum depression and with lactation difficulties, helping to prevent early weaning. Postnatal outpatient follow-up within the first two weeks is critical for the management of initial hypogalactia and prevention of early cessation of exclusive breastfeeding.